Challenges and Opportunities in Integrating AI into Human Resource Management Strategies - U. Amaleshwari, R. Shanmugapriya, (European Economic Letters (EEL), 2023)
Artificial Intelligence (AI) is something that can be used in every industry and profession including Human Resource Management. The integration of AI in HRM strategies can lead to the complete transformation of the business function. It is something that can be used by HR managers to improve productivity and performance at the workplace. AI can be leveraged by HR managers to improve recruitment & selection, training & development and employee retention. A higher level of automation can be achieved by the department with the integration of AI and in turn higher level of efficiency will be achieved. Although AI provides numerous opportunities to HRM strategies, there are still various challenges involved with the integration of AI in HRM. The aim of this research is to evaluate the challenges and opportunities involved with the integration of AI in HRM strategies. A systematic review has been done to gather the required insights and develop the article. Hence, the opportunities and challenges have successfully been outlined with the help of the systematic review.